2017
DOI: 10.1080/00380768.2017.1314829
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel silicate-solubilizing bacterial strainBurkholderia eburneaCS4-2 that promotes growth of japonica rice (Oryza sativaL. cv. Dongjin)

Abstract: The current study aimed to isolate and identify japonica rice (Oryza sativa L. cv. Dongjin) root-associated rhizobacteria and to investigate their ability to solubilize silicate, produce indole acetic acid (IAA), promote plant growth, and encourage silicon (Si) uptake and deposit in plants. A single bacterial isolate was selected on the basis of its silica-solubilizing ability and IAA production. The 16S rRNA gene sequence of the isolate identified it as Burkholderia eburnea CS4-2. Burkholderia eburnea CS4-2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 43 publications
4
52
0
1
Order By: Relevance
“…Microorganism mediated phosphate dissolution occurs through the production of various enzymes, such as phosphatase and phytase [11]. However, the acidolysis phenomenon has been reported for the dissolution of silicates [12]. There is evidence of the potential role of phosphate solubilizing bacteria (PSB) in the enhancement of plant growth through P uptake by plants.…”
Section: Of 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Microorganism mediated phosphate dissolution occurs through the production of various enzymes, such as phosphatase and phytase [11]. However, the acidolysis phenomenon has been reported for the dissolution of silicates [12]. There is evidence of the potential role of phosphate solubilizing bacteria (PSB) in the enhancement of plant growth through P uptake by plants.…”
Section: Of 12mentioning
confidence: 99%
“…The microorganisms isolated as described above were punched into petri plates with glucose agar medium (10 g L −1 glucose) containing 0.25% insoluble silicate (IS) (Mg 2 O 8 Si 3 ) to detect silicate solubilization and National Botanical Research Institute's Phosphate (NBRIP) medium with 0.25% insoluble phosphate (IP) [Ca 3 (PO 4 ) 2 ] using a wood pick and cultured at 30 • C for 24-168 h [12,14]. The clear zone formed was identified and the diameter was measured.…”
Section: Evaluation Of the Ability To Solubilize Insoluble Silicate Amentioning
confidence: 99%
See 1 more Smart Citation
“…feldspar, muscovite, biotite, and magnesium trisilicate with soluble phosphate sources (di-potassium hydrogen phosphate; K 2 HPO 4 and di-sodium hydrogen phosphate; Na 2 HPO 4 ); and agar based media containing glucose and magnesium trisilicate as sole source of nutrition (Sheng et al, 2008;Kang et al, 2017;Vasanthi et al, 2018). Number of bacterial strains of genus Bacillus, Pseudomonas, Proteus, Rhizobia, Burkholderia, and Enterobacter are known to release silicon from silicates and promote plant growth (Meena et al, 2014a;Wang et al, 2015;Kang et al, 2017;Kumawat et al, 2017;Chandrakala et al, 2019;Lee et al, 2019). However, due to the common mechanism of solubilization (organic acid production) and quantification method (molybdenum blue method) for both phosphate (P, Fiske and Subbarow, 1925) and silicon (Si, Elliott and Synder, 1991) there is unavailability of a concrete siliconsolubilizing media.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that applications of both B. mucilaginosus and A. niger could affect the content of available Si in various organs of the above-ground part of the rice plant (Figure 1). The absorption and accumulation of Si could be promoted, and the distribution of Si in the stems, leaves and spikes could be affected [55] . The content of available Si from high to low is ranked as: leaves, stems, spikes.…”
Section: Effects Of B Mucilaginosus and A Niger On The Nutrient Conmentioning
confidence: 99%